2022
DOI: 10.3847/1538-3881/ac641f
|View full text |Cite
|
Sign up to set email alerts
|

Planets Across Space and Time (PAST). III. Morphology of the Planetary Radius Valley as a Function of Stellar Age and Metallicity in the Galactic Context Revealed by the LAMOST-Gaia-Kepler Sample

Abstract: The radius valley, a dip in the radius distribution of exoplanets at ∼1.9 R ⊕, separates compact rocky super-Earths and sub-Neptunes with lower density. Various hypotheses have been put forward to explain the radius valley. Characterizing the radius valley morphology and its correlation to stellar properties will provide crucial observation constraints on its origin mechanism and deepen the understanding of planet formation and evolution. In this paper, the third part of the Planets Across Sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Water worlds, on the other hand, will not significantly change in size after formation since their sizes are dominated by their ice-silicate composition and not H/He-dominated atmospheres. Indeed, this demographic analysis has been performed in the works of, e.g., Berger et al 2020b, Sandoval et al 2021, and Chen et al 2022 show that the radius gap evolves on ∼100 Myr to Gyr timescales. Moreover, a recent study from Fernandes et al (2022) calculated occurrence rates for a sample of exoplanets around young stars.…”
Section: Discussionmentioning
confidence: 99%
“…Water worlds, on the other hand, will not significantly change in size after formation since their sizes are dominated by their ice-silicate composition and not H/He-dominated atmospheres. Indeed, this demographic analysis has been performed in the works of, e.g., Berger et al 2020b, Sandoval et al 2021, and Chen et al 2022 show that the radius gap evolves on ∼100 Myr to Gyr timescales. Moreover, a recent study from Fernandes et al (2022) calculated occurrence rates for a sample of exoplanets around young stars.…”
Section: Discussionmentioning
confidence: 99%
“…The radius gap has also been found to have some reliance on various other system properties such as orbital period, incident flux (Cloutier & Menou 2020), and stellar parameters as well (Fulton & Petigura 2018;Berger et al 2020b;Chen et al 2022). This was recently explored by Petigura et al (2022) for the sample of 1246 planets in the CKS (Petigura et al 2017b), which was the Kepler-focused predecessor to the TESS-Keck Survey.…”
Section: Radius Gapmentioning
confidence: 99%
“…We assumed solar metallicity for all systems. Metallicity does change stellar radius slightly, as well as possibly impacting the properties of sub-Neptunes above the radius gap (Chen et al 2022), but our spectra did not cover typical lines (e.g., Ca H and K or the Ca IR triplet) that can be used to measure metallicity at this spectral resolution; Lee et al 2008). In addition, we ran tests using model spectra of different metallicities and found that our results did not change significantly.…”
Section: Tablementioning
confidence: 85%